Diagnosis and Treatment of Sepsis in a Fourteen-year-old Patient: A case study of pulmonary inflammatory discharge without typical features of respiratory tract infection - Żaczek, Bartłomiej; Kozłowski, Jakub; Kamińska, Alicja; Kupczak, Wojciech; Bujak, Kinga; Kocjan, Aleksandra; Alsoubie, Ismael; Papachristoforou, Natalie; Kaźmierski, Wojciech; Ziomek, Mateusz; Lis, Paulina; Czubaj-Kowal, Marta (Journal of Education, Health and Sport, 2025)
Introduction and aim. Sepsis is a set of symptoms caused by the body’s uncontrolled inflammatory response to infection, leading to damage to more than one organ and homeostasis disorders. Symptoms of sepsis in children may be non-specific, making it difficult to diagnose quickly and effectively. Description of the case. This article presents the case of a 14-year-old patient who was admitted to the Paediatric Unit due to a high fever (up to 42 degrees Celsius) lasting from five days and severe pain in the area of the lower ribs on the left side, at the site of an injury that occurred two weeks earlier. Conclusion. In the case of unclear symptoms of high fever and indicators of inflammation, a broad diagnostic spectrum is necessary, including imaging and laboratory tests and specialist consultations. It is also important to consider the possibility of pulmonary congestion in case of postural pain and elevated levels of D-dimers. Regular patient monitoring and controlled laboratory studies are crucial in assessing the effectiveness of therapy and the progress of treatment.